Biodiversi-TEA—A quick and easy handling method for arthropod trap material in ethanol - Schweizer, Tanja; Wanke, Dominic; Haas, Michael; Krogmann, Lars (Zootaxa, 2020)
A quick and easy handling method for ethanol-preserved arthropods is presented, based on tea filter bags and holders. The method is especially suitable for short term storage of specimens resulting from Malaise traps, yellow pan traps and pitfall traps and can be used directly in the field, for subsequent transport and processing of specimens in the laboratory.